A scoping review of financial decision-making measures in midlife and beyond: results from the advancing reliable measurement in cognitive aging and decision-making ability (ARMCADA) study - Ho, Emily H.; Ece, Berivan; Bucko, Patricia; Karpouzian-Rogers, Tatiana; Pila, Sarah; Hosseinian, Zahra; Hussein, Yasmin; Han, S. Duke; Lichtenberg, Peter A.; Lim, Aaron C.; Weintraub, Sandra; Gershon, Richard C. (Frontiers in Psychology, 2025)
BackgroundCognitive decline in older adults affects key functions such as memory, concentration, planning, reasoning, and decision-making (DM). This decline in cognitive abilities compromises basic DM skills, with growing evidence that DM can decline before noticeable impairment or an official cognitive impairment diagnosis, adversely impacting quality of life and leading to negative outcomes in financial management and daily activities.ObjectiveThis scoping review aims to identify and evaluate existing measures of financial decision-making (FDM) abilities in clinical and community-dwelling populations aged 45 and older.MethodsWe conducted a systematic search in EMBASE (Elsevier), PsycINFO, PubMed, MEDLINE, PsychARTICLES, and Web of Science for studies published between January 2018 and November 2023. The multi-domain scoping review yielded 16,278 records. Title and abstract, as well as full-text screenings, respectively, were completed by two reviewers and conflicts were resolved by PhD level researchers. We then extracted data from the full-text articles.ResultsThe scoping review yielded 154 articles with 96 unique measures. The most frequently used measures were variations of the Iowa Gambling Task (IGT), The Legal Capacity for Property Law Transactions Assessment Scale (LCPLTAS), the Decision-making Competence Assessment Tool (DMCAT), the temporal discounting paradigm, and the Short Form version of the Financial Capacity Instrument (FCI-SF). Commonly used measures of financial decision-making (FDM) often assessed specific aspects, such as risk-taking behavior and basic financial knowledge.DiscussionMany of the FDM measures found in this scoping review were developed for use in laboratory settings, and less is known about potential for clinical use adaptation. Future work addressing this measurement gap could significantly enhance early interventions to ameliorate or mitigate decline, thereby improving financial management and quality of life for at-risk individuals.